2020
DOI: 10.3389/fcimb.2020.572570
|View full text |Cite
|
Sign up to set email alerts
|

Microbes in Tumoral In Situ Tissues and in Tumorigenesis

Abstract: Cancerous tumors are severe diseases affecting human health that have a complicated etiology and pathogenesis. Microbes have been considered to be related to the development and progression of numerous tumors through various pathogenic mechanisms in recent studies. Bacteria, which have so far remained the most studied microbes worldwide, have four major possible special pathogenic mechanisms (modulation of inflammation, immunity, DNA damage, and metabolism) that are related to carcinogenesis. This review aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 204 publications
0
4
0
Order By: Relevance
“…In GI cancers, the microbiota has been recognized to be related to chemotherapy, radiotherapy, and immunotherapy efficacy (7,8,12,13), indicating that the intestinal microbiota is a novel target to improve anti-tumor treatment (13). The presence of microbes within tumors and adjacent normal tissues may indicate disease progression and their potential roles in cancer pathogenesis (14)(15)(16). Understanding the alterations in the microbial community and abundance in GI organs thus aids in the study of GI cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In GI cancers, the microbiota has been recognized to be related to chemotherapy, radiotherapy, and immunotherapy efficacy (7,8,12,13), indicating that the intestinal microbiota is a novel target to improve anti-tumor treatment (13). The presence of microbes within tumors and adjacent normal tissues may indicate disease progression and their potential roles in cancer pathogenesis (14)(15)(16). Understanding the alterations in the microbial community and abundance in GI organs thus aids in the study of GI cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Further, an Massachusetts Institute of Technology (MIT) team found that mice infected with citrobacter murine were also more likely to develop colon cancer 104 . In 2003, Susan Erdman's team at MIT showed that H. pylori caused colon cancer in immune‐compromised mice 105 .…”
Section: Human Carcinogenic or Cancer‐promoting Microbiomesmentioning
confidence: 99%
“…103 Further, an Massachusetts Institute of Technology (MIT) team found that mice infected with citrobacter murine were also more likely to develop colon cancer. 104 In 2003, Susan Erdman's team at MIT showed that H. pylori caused colon cancer in immune-compromised mice. 105 In 2006, Erdman's team infected a particular mouse model with H. hepaticus and continued to observe subsequent changes in the mice.…”
Section: Gut Microbiomes and Crcmentioning
confidence: 99%
“…Evidence from a plethora of studies indicates that pathogenic microbes are responsible for over 20% of cancer cases [ 82 , 83 ]. In some cases, the microbiota was shown to influence cancer development by modulating inflammation signals and inducing genomic instability of host cells [ 84 , 85 ].…”
Section: Role Of the Human Microbiome In Tumor Development And Progre...mentioning
confidence: 99%
“…They observed a high abundance of Lactobacillus and Gardnerella in the female, while Corynebacterium, Staphylococcus, and Streptococcus are the most abundant urinary microbiota in the male [81]. Microbiota is the term used to describe a collection of microorganisms-viruses, bacteria, archaea, fungi, bacteriophage, and protozoans-specific to a particular body site or Microbiota is the term used to describe a collection of microorganisms-viruses, bacteria, archaea, fungi, bacteriophage, and protozoans-specific to a particular body site or Evidence from a plethora of studies indicates that pathogenic microbes are responsible for over 20% of cancer cases [82,83]. In some cases, the microbiota was shown to influence cancer development by modulating inflammation signals and inducing genomic instability of host cells [84,85].…”
Section: Role Of the Human Microbiome In Tumor Development And Progre...mentioning
confidence: 99%